The discoursal use of phraseological units - Arsenteva, Elena, 1956- (Cambridge Scholars Publishing, 2021)
The book is devoted to various problems of the discoursal use of phraseological units (PUs). It explores both core use and contextual use of such units, as well as different types of PU modifications, including addition, deletion, substitution, cleft use, phraseological pun, and extended metaphor, among others. In addition, the book also considers the translation of these modifications, which often present a very serious issue.